Aneurysms of pancreaticoduodenal arcade: Clinical profile and endovascular strategies. Issue 5 (8th July 2020) - Sharma, Supriya; Prasad, Raghunanadan; Gupta, Archna; Dwivedi, Pranav; Mohindra, Samir; Yadav, Rajanikant R
Abstract: Background and Aim: Pancreaticoduodenal arcade aneurysms (PDAAs) are uncommon lesions associated with a significant risk of rupture and mortality. This study describes the etiology, clinical presentation, and endovascular management strategies of PDAAs across a spectrum of indications. Methods: The clinical records of patients with PDAAs referred for endovascular management from January 2018 till November 2019 were retrospectively reviewed. Data on presenting symptoms, associated etiologies, and outcomes after endovascular treatment were collected and studied. Results: We found 15 patients with false and 1 patient with true aneurysm of pancreatoduodenal arcade (PDA). The associated conditions were coeliac artery stenosis, severe necrotizing pancreatitis, and chronic pancreatitis or iatrogenic (postendoscopic papillotomy and percutaneous metallic biliary stenting). The main presenting feature was gastrointestinal bleed, while 2 patients had abdominal pain and 1 had gastric outlet obstruction. A multiphase computed tomography scan demonstrated the ruptured aneurysm in all patients. Site of origin of PDAA influenced the choice of transarterial endovascular strategy (coiling for aneurysms of main trunk of arteries and glue injection for those arising from small arterial branches). This was carried out in an emergency setting for 12 patients and as an elective procedure in 4 patients. Technical success was demonstrated in all patients and clinical success in 14. The two patients who had rebleed were salvaged by repeat endovascular procedure. Postembolization syndrome was seen in three patients. Conclusions: With advancing technology, endovascular strategies continue to evolve. Careful attention to ensure hemodynamic resuscitation and stability, correction of pre‐existing coagulopathy and attention to technique can lead to the possibility of endovascular approaches as a dependable option in the management of ruptured PDAAs. Abstract : Aneuryms of the pancreatoduodenal arcade are potentially lethal with rising incidence. They can have varied presentations, rupture being potentially life threatening. Endovacsular strategies provide effective minimally invasive management option.